In-Vitro Effect of Effectively of G-Bond and Z-Prime Plus in Prevention of Fracture of Prefabricated Zirconia Posts Bonded to Root Canal Walls - Hafza Mahnoor Kaleem, Rizwan Qureshi, Waleed Javaid Toosy, Muhammad Imtiaz, Muhammad Farooq (Pakistan Journal of Medical & Health Sciences, 2023)
Background and Aim: The purpose of this research was to examine the influence of Z-Prime Plus and G-Bond on zirconia posts fracture resistance affixed to the walls of root canals. Place of Study: Avicenna Medical College Lahore Study Duration: March 2021 to April 2022 Materials and Methods: In this in-vitro experimental study, the diameter and length of each of the 20 mandibular premolars used were identical. This assured that the study’s findings were comparable. Once a cut was made at the cementoenamel junction (CEJ) to prepare the teeth for root canal therapy, the teeth were randomly assigned to one of two groups (n=11) with the same number of teeth in each group. In the experiment, a single tooth from each group was chosen at random to serve as the control. A post space of approximately 10 millimeters in length was established in the remaining teeth. The following process involved etching the intracanal dentin, followed by rinsing and drying the material. The technique involved filling the canal with Panavia F2 resin cement. After applying G-Bond and Z-Prime Plus to the zirconia posts in respectively, groups 1 and 2, the placement of post was done in the canals and subsequently cemented. The photo core resin composite material was utilized in the fabrication of the cores. The longitudinal axis of the teeth was compressed by a force application to the core of central fossa o at a crosshead speed of 0.5 millimeters per minute. This was accomplished with a crosshead speed of 0.5 mm/min. The load that caused the fracture was measured and documented. To analyze the data, a t-test was conducted, and a normal distribution was also taken into account. Result: The results indicated that the average fracture resistance of G-Bond was 1088.1±330 while the average fracture resistance of Z-Prime Plus was 898.4±369 however, the difference was not statistically significant (P=0.3). Practical Implication: The influence of Z-Prime Plus and G-Bond on zirconia posts fracture resistance affixed to the walls of root canals Conclusion: There was no significant difference between the fracture resistance of zirconia posts bound with G-Bond and Z-Prime Plus to root canal walls. In contrast, G-Bond is highly advised for usage in this application due to its decreased coefficient of variation (CV) and significantly increased fracture resistance. This makes it a great option for the current endeavor. Keywords: Primer; resin composite; shear bond strength; zirconia ceramic, G-Bond, Post and Core Technique, Z-Prime Plus